PENGARUH PEMBERIAN KRIM EKSTRAK BAWANG MERAH (ALLIUM CEPA L.) TERHADAP PROSES PENYEMBUHAN LUKA BAKAR PADA TIKUS PUTIH (Rattus Novergicus) - Nurul Hidayah; Asih Rahayu; Adhitya Yoppy Ro Candra; Kurnia Latif (VITEK : Bidang Kedokteran Hewan, 2019)
This study aimed to determine the influence of onion extract cream (Allium cepa) for burning burns in white rats (Rattus norvegicus). The research was experimental with a concentration of 45%, 50%, and 55% onion Cream Extract (Allium cepa). The Data can then be processed using the Kruskall Wallis test. From the statistical test results, each level of Bakart wound showed noticeable difference. The P < 0.05 is thus distinct from P1, P2, and P3. At the level of fluid burns Sig 0.000, because (P < 0.05) There were noticeable difference in the treatment of PO with P1, P2, and P3. The conclusion of this study of the introduction of onion extract Cream (Allium cepa.) can be used for wound healing in white rats (Rattus norvegicus).